Delineating Subjective Experiences in the Mardika Market: Self-Management of Beggars Identities in Moluccas, Indonesia - Darma, Darma; Malawat, Mahdi; Ridwan, M. (Technium Social Sciences Journal, 2021)
Mardika market is a strategic location for people engaging in begging activity in Moluccas, Indonesia. A beggar is a person who earns an income in public in various ways and hopes to expect mercy from others, and engages in activities by taking advantage of to make other people feel sorry for them. The research aims to explore the self management of people carrying out begging activities. This study uses a subjective interpretive method through a phenomenological approach based on the theory of symbolic interaction. The results demonstrate that beggars verbally self-management impressions. Nonverbally, beggars with dirty clothes, sad faces, and slow gestures remove their hands using bowls as a sign of asking. Their self-management front appearance takes advantage of physical backwardness, pretending to be disabled, and living a poor and wandering life so that they deserve pity. This differs from a figure who has a robust physical condition, carries out everyday activities, wears proper clothes, displays a cheerful face, and has good social relations with family and society in the self-management behind appearance.